Tijaniyah Sufi Order's Contribution to Social Righteousness Practices - Adnan, Adnan; Rahman, Mohammad Taufiq; Jamaludin, Adon Nasurullah (Hanifiya: Jurnal Studi Agama-Agama, 2024)
This research delves into a Sufi Order’s significant role in fostering social piety among its followers. Rooted in Sufism, the Tijaniyah Order (Tariqa) emphasizes a dual focus on spiritual relations with Allah (hablum minallah) and social contributions (hablum minannas). Social piety, in this context, involves embodying religious values in everyday life, such as performing good deeds, assisting those in need, and fulfilling social responsibilities. The study employs a qualitative methodology, incorporating participatory observation, in-depth interviews, and documentary studies. Data analysis follows a rigorous process of reduction, presentation, and verification to draw valid conclusions. Central to this research are the Tazkiyatun Nafs (soul purification) concepts of Takhalli, Tahalli, and Tajalli. Takhalli refers to purging oneself of negative traits like greed and selfishness, thereby heightening sensitivity to social needs. Tahalli involves cultivating positive attributes like compassion and kindness, which encourage proactive social engagement. Tajalli represents achieving a profound realization that social actions reflect divine love. The Tijaniyah Tariqa's blend of spiritual and social values significantly contributes to societal welfare and harmony. Continuous practices such as amaliah wirid lazimah, wadhifah, and hailalah reinforce values like trust, honesty, almsgiving, and cooperation. This integration fosters harmonious social interactions, underscoring the Tijaniyah Tariqa's enduring and meaningful impact on social welfare. Through its presence at Al-Falah Islamic Boarding School, of Biru, Garut Regency, West Java, Indonesia, the Tijaniyah Tariqa not only strengthens individual spirituality but also enhances social bonds, leaving a positive mark on the community.